THE INFLUENCE OF DIGITAL MEDIA ON READING AND WRITING PRACTICES - Jumabayeva Mahzunabonu; Abdurahmonov To'raxon (TADQIQOTLAR.UZ, 2024)
In the digital age, media has revolutionized the way people access information, communicate,  and  express  themselves.  The  rapid  development  of  digital  media, including  smartphones,  tablets,  e-books,  and  social  platforms,  has  had  a  profound impact on reading and writing practices. This article explores how digital media shapes literacy habits, challenges traditional practices, and offers new opportunities for both reading and writing.